2014
DOI: 10.1017/s0007114514002207
|View full text |Cite
|
Sign up to set email alerts
|

The association between obesity and fluid intelligence impairment is mediated by chronic low-grade inflammation

Abstract: Published evidence suggests that obesity impairs cognition. Development of chronic low-grade inflammation (CLGI) represents the earliest consequence of obesity. The present study investigated the association between obesity and fluid intelligence impairment and assessed the potential mediating role of CLGI and psychological (depression/anxiety symptoms), lifestyle (exercise) and physiological (metabolic dysfunction indices) factors in this association. Clinically healthy participants (n 188), grouped as per BM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 71 publications
3
29
0
1
Order By: Relevance
“…; Spyridaki et al . ), the concentrations of CRP, the most conventional and robust marker of chronic low‐grade inflammation in obesity (Aronso et al . ; Ishii et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…; Spyridaki et al . ), the concentrations of CRP, the most conventional and robust marker of chronic low‐grade inflammation in obesity (Aronso et al . ; Ishii et al .…”
Section: Discussionmentioning
confidence: 99%
“…; Spyridaki et al . ). A previous study reported that individuals with obesity have lower neural activity in the parietal cortex compared with normal‐weight individuals in resting conditions (Karhunen et al .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous studies have also linked energy balance-related factors, such as obesity and physical activity (PA), to aging-related cognitive decline [7, 8]. Physiological consequences of obesity such as chronic inflammation, hypertension, hyperlipidemia, insulin resistance and subsequent diabetes, have deleterious effects on innate immunity, which in turn directly harm the central nervous system [9]. PA, a factor interrelated with body fat, may help maintain cognitive function in elders, through enhancing cardiovascular health, helping decrease brain dysfunction and neurodegeneration caused by inflammation, lowering amyloid loading, increasing levels of neurotransmitters and insulin-like growth factor I, etc [10].…”
Section: Introductionmentioning
confidence: 99%
“…и соавт. было выявлено, что именно повышение высокочувствительного С-реактивного белка, СОЭ и фибриногена ассоции-ровалось с нарушением когнитивных функций [33]. В соответствии с экспериментальными данными глиоз был выражен в медиобазальной части гипота-ламуса [34].…”
Section: воспаление как фактор развития когнитивных нарушенийunclassified